Factors and mechanisms of arterial hypertension development in patients with atherosclerosis of lower limb arteries - E. M. Evsikov; V. I. Vechorko; N. V. Teplova; M. H. Zhapueva; N. G. Artamonova (Кардиоваскулярная терапия и профилактика)
The article contains information about the frequency of development of arterial hypertension (AH), the features and causes of its development in patients with peripheral atherosclerosis. AH in patients with chronic atherosclerotic diseases of lower limb arteries and acute thrombotic occlusion complicates the course of this pathology. In most patients, the opinion that AH associated with atherosclerosis due to affection of renal arteries is generally accepted. Currently, an important practical question remains about the possible negative impact of intensive antihypertensive therapy with a significant reduction in blood pressure and aggravation of necrobiosis processes in the ischemic limb in a patient with acute arterial thrombosis.